The effectiveness of iot-based learning media for supporting the expertise program of renewable energy engineering in vocational high school - Kayohana, Ketut Widya; Asnawi, Rustam; Amaria, Marshanda Alfa (Jurnal Pendidikan Teknologi dan Kejuruan, 2023)
The objectives of this study are: (1) the performance of developing renewable energy based on IoT (Internet of Things) in the renewable energy engineering expertise program in the subject of solar hydro-wind energy (Tesha) engineering at Vocational Schools, (2) the level feasibility of development renewable energy based IoT in the subject Tesha's learning at Vocational Schools, (3) level effectiveness development renewable energy based IoT in the subject Tesha learning at Vocational Schools. This research is a research and development research with ADDIE approach (Analyze, Design, Develop, Implement, Evaluate) (Branch (2009) with approach experiments that will used is Quasi Experimental Design with form Nonequivalent Control Group Design. Results from study this show: (1) the feasibility of learning media " Eligible " category. Analysis response user get "Very feasible " category with Cronbach's Alpha get "Very Strong" category so that this media is declared fit for use as a learning media, (2) different and difficulty test on the questions pre-test with medium category of 96.875%, difficult 3.125% and post-test with moderate category of 93.75%, easy 3.125%, and difficult 3,125%, (3) Learning media more IoT based effective in comparison without using IoT because score statistic 0.05 that is 0.044 with the post-test average value is greater than the specified KKM value (85.42 75), while without using IoT, the post-test average value almost same KKM value (75.96 75).Keywords: learning media, renewable energy, Internet of Things (IoT)